Pengaruh Penambahan Polyvinylpyrrolidone Pada Proses Kristalisasi Terhadap Sifat Tabletabilitas Gemfibrozil - Denar Rera Fatqia (Fakultas Farmasi Universitas Jember, 2025)
This study aims to investigate the effect of adding PVP K90 in the crystallization process on the tabletability properties of gemfibrozil, a fibrate drug used to treat hypertriglyceridemia. Gemfibrozil is known for its effectiveness in lowering triglyceride levels; however, it exhibits poor tabletability properties, which can adversely affect its quality and effectiveness. In this research, 20 grams of gemfibrozil were dissolved in 50 mL of ethanol, followed by the addition of PVP K90 at varying concentrations of 0.5%, 1.0%, and 1.5%. The crystallization process was conducted using the solvent evaporation method, and characterization was performed using PXRD, FTIR, DSC, and light microscopy. The results indicated that the gemfibrozil - PVP K90 crystals were rodshaped, with distinct melting points observed at not different PVP K90 concentrations. The moisture content evaluation revealed that the moisture level of pure gemfibrozil was 1.551% ± 0.290, while the moisture levels for gemfibrozil - PVP K90 crystals at concentrations of 0.5%, 1.0%, and 1.5% were 2.974% ± 0.240, 3.469% ± 0.359, and 3.730% ± 0.195, respectively. Furthermore, tensile strength testing showed a significant increase after the addition of PVP K90, with the tensile strength value at a pressure of 1.0 ton reaching 1.060 ± 0.025 N/mm² for a concentration of 1.5%. Statistical analysis using SPSS confirmed that the observed difference was significant (p< 0.05). In conclusion, the addition of PVP K90 in the crystallization process of gemfibrozil significantly increased tensile strength.
Reuploud file repositori 9 Apr 2026_Firli_tata
Keywords: Gemfibrozil; PVP K90; Tabletability; Crystallization; Tensile strength.